Визначення та опис технічної енергетичної системи з використання відновлюваних ресурсів плодових насаджень - Караєв, Олександр Гнатович; Караев, Александр Игнатьевич; Karaiev, Oleksandr; Бондаренко, Лариса Юріївна; Бондаренко, Лариса Юрьевна; Bondarenko, Larysa (My University, 2019)
UK: У статті наведено опис технічної енергетичної системи вироблення енергопродукту із зрізаних гілок плодової деревини і проведено її аналіз. Встановлено, що зрізані гілки плодових дерев можна віднести до відновлюваного ресурсу, який може бути перетворений в певний вид енергопродукту. Представлено інформаційну модель використання відновлюваних ресурсів плодових насаджень і визначено види технологій їх перетворення. Визначено об’єм деревини зрізаних гілок плодових культур, що дозволяє встановити орієнтовний їх об’єм окремого господарства. RU: в статье наведено описание технической энергетической системы выработки энергопродукта из срезанных веток плодовой древесины и проведен ее анализ. Установлено, что срезанные ветки плодовых деревьев можно отнести к возобновляемым ресурсам, которые могут быть преобразованы в определенный вид энергопродукта. Представлена информационная модель использования возобновляемых ресурсов плодовых насаждений и определены виды технологий их переработки. Определен объём срезанных веток конкретного вида плодовых культур, который позволяет определить ориентировочный их объем отдельно взятого хозяйства вцелом и принять решение о производстве определенного вида энергопродукта. EN: The description of the technical power system of the production of energy products from cut branches of fruit trees is given in the article as well as its analysis has been carried out. It has been noted, that the cut branches of fruit trees can be attributed to a renewable resource, which can be transformed into a certain type of energy product. In case when the structure of fruit crops growing technology has a technical energy system for the production of energy products, then such production entities may become not only consumers of energy products, but their suppliers as well. The information model of renewable resources of fruit plantations is presented and the types of technologies of their transformation are defined. The volume of cut timber cuttings has been determined: fruiting plantations - 8 t/ha; young plantings - 1.8 t/ha. These data enables to determine the approximate volume of cut branches of fruit crops of a separate economy and make decision on the development of a particular type of energy product. It has been defined, that the processing of branches into briquettes has the energy intensity of 2 MJ/kg, and the specific heat of their combustion is about 10 MJ/kg. It testifies that the energy efficiency of using renewable resources serves as a "biofuel". To improve the bourse method of "bio-fertilizers" manufacturing the thermodynamic model for composting process has been developed. It enables to optimize the parameters of burts, taking into account certain energy losses when composting wood chips of 10 tons: the length of the burt should be 6,4 m, and its surface area should be 32 m2. It has been noted, that the transformation of the cut branches into "bio-methane" needs the development of the method for optimizing the duration of the biogas generator operation cycle. The scheme of energy product development has been worked out as well as it was proved that it is the basis for making the complex model of the process for fruit garden renewable resource use.
Определение и описание технической энергетической системы использования возобновляемых ресурсов плодовых насаждений
Defining and description of technical energy system for using renewable resources of fruit plantations
Keywords: відновлюваний ресурс; енергопродукт; зрізані гілки; плодовий сад; технічна енергетична система